Instant Messaging and Interruption: Influence of Task Type on Performance - Czerwinski, Mary; Cutrell, Ed; Horvitz, Eric (Association for Computing Machinery, Inc., 2000)
We describe research on the effects of instant messaging (IM) on ongoing computing tasks. We present a study that builds on earlier work exploring the influence of sending notifications at different times and the kinds of tasks that are particularly susceptible to interruption. This work investigates alternative hypotheses about the nature of disruption for a list evaluation task, an activity we had identified as being particularly costly to interrupt. Our findings replicate earlier work, showing the generally harmful effects of IM, and further show that notifications are more disruptive for fast, stimulus-driven search tasks than for slower, more effortful semantic-based search tasks.
OZCHI 2000 Conference Proceedings